2011
DOI: 10.1007/s12215-011-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

A note on the Hausdorff dimension of general sums of pulses graphs

Abstract: In this work we study the some general fractal sums of pulses defined in R by:where (a n ), (λ n ) two positive scalar sequences such that a n is divergent, and (λ n ) is non-increasing to 0, G is an elementary bump and X n are independent random variables uniformly distributed on a sufficiently large domain Ω. We investigate the Hausdorff dimension of the graph of G and in particular we answer a question given by Tricot in (Courbes et dimensions fractales, Springer, Berlin, 1995).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…See also [3] for the box dimension of G , or [43,45] for a more systematic study of graph dimensions. When α < h, almost surely dim…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…See also [3] for the box dimension of G , or [43,45] for a more systematic study of graph dimensions. When α < h, almost surely dim…”
Section: Introductionmentioning
confidence: 99%
“…Calling the graph of the process G and its box-dimension, they showed that as soon as there exists an interval I on which (the space of global Hölder real functions of exponent H ) and is -diffeomorphic on some interval, then almost surely See also [ 3 ] for the box dimension of , or [ 43, 45 ] for a more systematic study of graph dimensions. When , almost surely .…”
Section: Introductionmentioning
confidence: 99%